History, Oral History and Archaeology: Reinterpreting the “Boat Places” of Erebus Bay - Stenton, Douglas R.; Park, Robert W. (ARCTIC, 2017)
Historical and archaeological records are examined for three archaeological sites at Erebus Bay, King William Island, associated with the 1845 John Franklin expedition. Comparison of 19th century historical descriptions with archaeological data from sites NgLj-1 and NgLj-3 establishes that the identification of NgLj-1 as the site of the 1859 McClintock “boat place” is incorrect and that NgLj-3 is the actual site. An assessment of 19th century oral historical information and contemporary archaeological data from NgLj-2 supports the conclusion that a ship’s boat from the Franklin expedition was once located at the site, but its identification as the second “boat place” discovered by Inuit in 1861 is problematic. The study underscores interpretive risks associated with uncritical acceptance of historical and oral historical accounts and the importance of archaeological research in the reconstruction of events surrounding the fate of the Franklin expedition. Des enregistrements historiques et archéologiques de trois sites archéologiques de la baie Erebus, île King William, sont examinés en lien avec l’expédition de John Franklin en 1845. La comparaison des descriptions historiques du XIXe siècle avec les données archéologiques des sites NgLj-1 et NgLj-3 permet d’établir que l’identification de NgLj-1 comme site de l’« emplacement du bateau » de McClintock en 1859 est incorrecte et que NgLj-3 est le vrai site. L’évaluation d’information historique orale du XIXe siècle et de données archéologiques contemporaines de NgLj-2 vient appuyer la conclusion selon laquelle un bateau du navire de l’expédition a déjà été repéré au site, mais son identification en tant que deuxième « emplacement du bateau » découvert par les Inuits en 1861 est problématique. Cette étude fait ressortir les risques d’interprétation liés à l’acceptation exempte de critiques de données historiques ou de récits oraux historiques de même que l’importance de la recherche archéologique dans la reconstruction des événements entourant le sort de ...